Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Where is the Ethical Debate around Phenotypic Screening of Prenatal Tissue Using Stem Cell-Derived Tissue Constructs? - Alexander R. Harris; Mary Jean Walker; Frederic Gilbert; Patrick McGivern (Stem Cell Reviews and Reports, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Stratification of polyisocyanate in two-component waterborne polyurethane films - Yang Liu; Kenneth Tran; Kevin Ho; Tianjia Yang; Xiaochong Li; Sze Hang Wong; Margaret Zhang; Gilbert Walker; Frédéric Lucas; Mitchell A. Winnik (Chemical Engineering Journal, 2024)

Extinction dynamics: The interplay of species traits and the spatial scales of metapopulation declines - Emma J. Walker; Benjamin Gilbert (Ecology, 2023)
Global changes can lead to species declines and extinctions through their impacts on species habitats at two distinct spatial scales: habitat destruction, in which individual habitat patches are destroyed by land‐use change or natural disasters, and habitat degradation, in which larger scale changes, such as nitrogen deposition or climate change, lower mean population abundances across landscapes. We developed a theory showing that, even when these two forms of global change have an identical impact on a species' total amount of habitat, they have qualitatively different consequences for species dynamics and extinction. Using metapopulation theory and simulations, we found distinct impacts of these global changes characterized through several responses: the rate at which populations are lost from the remaining patches, extinction thresholds, and the duration of extinction debts. Habitat degradation causes a faster decline in species populations when habitat reduction is low, making it particularly detrimental for rare species. Habitat destruction has smaller impacts for low habitat reduction, but shows clear thresholds beyond which it surpasses degradation's negative impact; the location and steepness of the threshold depends on species dispersal, with poor dispersers having steeper thresholds. These results highlight the challenge of using population monitoring to assess the consequences of global changes and predict consequences of further change: extinction trajectories cannot be predicted due to thresholds (habitat destruction) and lagged dynamics that lead to extinction debts (habitat degradation). Our research clarifies why the impacts of one type of global change may poorly predict the impacts of the other and suggests general rules for predicting the long‐term impacts of global changes based on species traits.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

The control of marine biofouling on xerogel surfaces with nanometer-scale topography - Nikhil Gunari; Lenora H. Brewer; Stephanie M. Bennett; Anastasiya Sokolova; Nadine D. Kraut; John A. Finlay; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Frank V. Bright; et al. (Biofouling, 2011)

Barnacle settlement and the adhesion of protein and diatom microfouling to xerogel films with varying surface energy and water wettability - John A. Finlay; Stephanie M. Bennett; Lenora H. Brewer; Anastasiya Sokolova; Gemma Clay; Nikhil Gunari; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Michael R. Detty (Biofouling, 2010)

The role of surface energy and water wettability in aminoalkyl/fluorocarbon/hydrocarbon-modified xerogel surfaces in the control of marine biofouling - Stephanie M. Bennett; John A. Finlay; Nikhil Gunari; David D. Wells; Anne E. Meyer; Gilbert C. Walker; Maureen E. Callow; James A. Callow; Frank V. Bright; Michael R. Detty (Biofouling, 2009)

Nanoscale structures and mechanics of barnacle cement - Ruby May A. Sullan; Nikhil Gunari; Adrienne E. Tanur; Yuri Chan; Gary H. Dickinson; Beatriz Orihuela; Dan Rittschof; Gilbert C. Walker (Biofouling, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Calcitonin is expressed in the chicken pituitary gland: influence of gonadal steroids and sexual maturation - Sreenivasa R. Maddineni; Susan M. Krzysik-Walker; Olga M. Ocón-Grove; Susan M. Motch; Gilbert L. Hendricks; Ramesh Ramachandran (Cell and Tissue Research, 2007)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)